Accuracy of early warning scores for predicting clinical worsening in COPD patients - Enrique Castro-Portillo; Joan B. Soriano; Raúl López-Izquierdo; Carlos del Pozo Vegas; José L. Martín-Conty; Irene Sánchez Soberón; Juan F. Delgado Benito; Begoña Polonio-López; Manuel Sánchez-de-la-Torre; Miguel Á. Castro Villamor; Ancor Sanz-García; Francisco Martín-Rodríguez (ERJ Open Research)
Background COPD, a condition whose acute exacerbations (AECOPD) are commonly faced by the emergency medical services (EMSs), could modify the performance of early warning scores (EWSs). Our objectives were to assess the 2-day mortality predictive performance of five EWSs in patients with baseline COPD managed by an EMS with unselected acute diseases and to compare the EWS performance between those with AECOPD and those without. Methods This was a prospective observational study of adults (age >18 years) with a previous COPD diagnosis who were admitted to and transferred to the emergency department by the EMSs due to an unselected acute disease, whether AECOPD or other according to the emergency medical team. Demographics, vital signs for the five EWSs (National Early Warning Score 2 (NEWS2), quick Sequential (Sepsis-related) Organ Failure Assessment (qSOFA), quick COVID-19 Severity Index (qCSI), CURB-65 score for pneumonia severity and BAP-65 score for AECOPD) calculations and outcomes (hospital and intensive care unit (ICU) admission and 2-day mortality) were collected. Results A total of 1703 patients with COPD were selected: 524 with AECOPD and 1179 without. NEWS2 presented the highest predictive capacity for the global, AECOPD and non-AECOPD cohorts: area under the curve 0.880 (95% CI 0.84–0.91), 0.775 (95% CI 0.68–0.86) and 0.913 (95% CI 0.86–0.96), respectively. Conclusions NEWS2 was the best predictive model for COPD, presenting excellent performance for the global and non-AECOPD cohorts but a decreased performance for the AECOPD cohort. Therefore, NEWS2 may aid in EMS decision making through appropriate risk assessment, but its use in COPD patients with AECOPD should be handled with care due to decreased performance.